#TITLE_ALTERNATIVE# - Supriadi (NIM 236 98 012), Heru
Abstract : This design is expected to have an economic value and its performance can competed with others fans in local or global market. This fans performance can be optimized just if all of elements can be formulated accurately. Those elements are profile, planform, twist distribution and blade numbers. Instead of optimization, aproximation in performance analysis and geometry design are taken to gain simplicity in manufacturing aspects. Golden Axial Fan type D/400/1.5 as the reference to define fans diameter. Blade Element Theory and Velocity Triangle Diagram are applied computationally. From this computation process, 2 (two) configurations are generated. They are blade planform with twist and without twist. Blade planform with twist is generated by distributing linearly the length of the flap chord from hub to tip with uniformly deflection angle. Experimental investigation was conducted to both configurations at 1: 1 scale.